Students’ Perceptions Toward Feedback from Their Teachers and Peers in Writing Activities by Considering Their Writing Anxiety - Annisa Astrid (Jadila: Journal of Development and Innovation in Language and Literature Education, 2023)
The objective of this study was to investigate the perceptions of students with varying levels of writing anxiety regarding the learning activities associated with using teacher feedback and peer feedback. The present study utilized a quantitative approach for data collection. The quantitative data were obtained through a survey administered to 46 students in the English Department of a state Islamic University. The quantitative data were subsequently analyzed using descriptive statistics, specifically percentages and frequency, and non-parametric analysis employing the Mann-Whitney test. The findings indicated no statistically significant difference in the perceptions of students who experienced writing anxiety and received instruction through either teacher or peer feedback. Essentially, students who demonstrate lower levels of writing anxiety display a cheerful disposition towards the incorporation of both teacher feedback and peer feedback. During the intervening period, discernible differences arose in the viewpoints of students demonstrating heightened writing anxiety levels who were provided with instructions through teacher feedback instead of peer feedback